Überblick über wichtige zivilrechtliche Entscheidungen des japanischen Obersten Gerichtshofs aus dem Jahr 2004 - Schüßler-Langeheine, Dirk; Hafermalz, Eberhard (Zeitschrift für Japanisches Recht, 2006)
The authors give an overview of important Supreme Court decisions in 2004 dealing with property law; contract law, in particular, assignments in the context of insolvency proceedings, commercial loans, and lease contracts; the law of unjust enrichment; tort law; law of succession; company law; commercial transactions; insurance law; labor law; intellectual property law, including licences; and the law of procedure, in particular regarding the admission of evidence, preliminary injunctions, and insolvency proceedings. (The Editors)